Matemática: computador para quê? - ALMEIDA, Carmem Lucia Brito Souza de (2006)
The present work shows the research results carried on five academic institutions of the State of Pará, Brazil. We present the opinion and feeling of students and teachers with respect to the use of the computer in the teaching of Mathematics, having Tikhomirov theories as backgrounds. Through a counter point between Instructionism and Constructionism, we are leaded to favor Constructionism. By the end, we present an elaborated reflection about the role of the computer in the teaching of Mathematics.